Biopolityka wobec wyzwań postępu technologicznego w medycynie - Skrzypczak, Jędrzej (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The issues associated with biopolitics are the cause of great controversies, making the concept almost ‘taboo’ these days. Current progress in medical technology has brought immense benefits to the whole of humanity, but it can also cause threats. The subject of this paper is to draw readers’ attention to the issues and threats related to the progress of medical technology. Biopolitics has produced various, frequently perilous, outcomes, therefore it is emphasized that biopolitical phenomena should always have a legal and moral dimension. In many cases, the realm of human biology and nature is impacted to an inconceivable degree, thus biopolitics is challenged by having to answer many significant questions, requiring the development of a cohesive state policy in this field and the provision of a legal framework for such activities.